2000
DOI: 10.1097/00006842-200011000-00004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Life Events on Cardiovascular Reactivity to Behavioral Stressors As a Function of Socioeconomic Status, Ethnicity, and Sex

Abstract: The attenuating effects of stressful life events on cardiovascular reactivity in response to car-driving simulation in youths are consistent with an inoculation effect, whereas the potentiating impact of stressful life events on reactivity observed during the social stressor interview is compatible with a possible cost of coping effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 28 publications
4
34
1
Order By: Relevance
“…A particularly interesting longitudinal study showed that maternal education was inversely related to childhood resting blood pressure at ages 7 and 9 years, but then had no association among 11-and 15-year-olds (Howe et al 2013). When exposed to an acute stressor, SED adolescents exhibit dampened rather than elevated blood pressure reactivity Musante et al 2000). Other studies have failed to reveal any association between SED and blood pressure reactivity in adolescents (Chen et al 2002).…”
Section: Physiological Systemsmentioning
confidence: 96%
“…A particularly interesting longitudinal study showed that maternal education was inversely related to childhood resting blood pressure at ages 7 and 9 years, but then had no association among 11-and 15-year-olds (Howe et al 2013). When exposed to an acute stressor, SED adolescents exhibit dampened rather than elevated blood pressure reactivity Musante et al 2000). Other studies have failed to reveal any association between SED and blood pressure reactivity in adolescents (Chen et al 2002).…”
Section: Physiological Systemsmentioning
confidence: 96%
“…Subsequently, we tested the hypothesis that carriers of the GNB3 825T allele would exhibit high resting BP and exaggerated BP reactivity to behavioral stress. A total of 532 young subjects (268 whites, 264 blacks, aged 20.4 y) performed two acute stressors, including car simulation driving and social competence interview, each of which lasted for 10 minutes [19]. We used a multivariate regression approach and found a significant carrier status by race interaction for resting BP (P < 0.05).…”
Section: Blood Pressure Reactivitymentioning
confidence: 99%
“…14,16 Subjects also completed a brief battery of lifestyle questionnaires assessing stressful life events, physical activity, smoking, drug usage, and anger coping styles. 18,19 Subjects were prepared for the hemodynamic evaluations through the use of the Dinamap vital signs monitor (model 1864SX; Critikon) and the NCCOM-3 (BoMed Medical Manufacturing, Ltd) continuous thoracic bioimpedance monitor, which measured heart rate and cardiac output. An appropriately sized BP cuff was placed on the right arm.…”
Section: Protocolmentioning
confidence: 99%